Analysis on the Contributions and Dedication of Amrah binti Abdul Rahman as a Muhaddithah in Seeking Knowledge - Hamisan@Khair, Nur Saadah; Mohd Shukri, Nur Izzah (Semarak International Journal of Islamic Studies and Culture, 2025)
Muhaddithat refers to female hadith transmitters who were equally skilled as their male counterparts in narrating and transmitting hadith collections. Their invaluable contributions to the preservation and transmission of the Prophetic Hadith have been widely acknowledged, including by Western scholars. While previous discussions on Muhaddithat have been extensive, studies focusing on specific female scholars, such as Amrah binti Abdul Rahman, remain limited. This research aims to fill this gap by exploring Amrah’s biography, her intellectual journey, and her significant role as a Muhaddithah. Employing a qualitative methodology, the study analyses historical texts, biographical dictionaries, and hadith compilations to construct a comprehensive understanding of her life and contributions. The findings reveal Amrah’s exceptional dedication to seeking and disseminating knowledge, her scholarly influence, and her vital role in maintaining the authenticity of the Prophetic traditions. This study highlights the importance of recognizing female scholars like Amrah binti Abdul Rahman in Islamic intellectual history and their enduring legacy in the field of hadith studies.